Prediction of the feeding background of Iberian pigs using the fatty acid profile of subcutaneous, muscle and hepatic fat. (Meat science, 1998)
Thirty Iberian pigs weighing 95 kg were randomly distributed into three groups of 10 animals each and fattened in three traditional management systems ['montanera' (MO), fed extensively on acorns, 'cebo' (CE) fed on a commercial diet and 'recebo' (RE), fed on acorns and a commercial diet]. Fatty acids from the Masseter muscle, lard and liver were analysed. In the lard, fatty acid profiles from MO and RE pigs presented minor differences; however, in the liver, RE pigs showed differences to MO pigs in most of the fatty acids studied. This suggests that the muscle and especially the liver fatty acid profile reflects the feeding regime during the last phase of feeding, while the lard reflects longer term differences.